2012
DOI: 10.5350/dajpn2012250202
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of interpersonal schemas, perfectionism, and thought action-fusion in obsessive-compulsive disorder / Obsesif-kompulsif bozuklukta kişilerarası şemalar, mükemmeliyetçilik ve düşünce-eylem kaynaşmasının yordayıcı rolü

Abstract: Researches ABSTRACTThe predictive value of interpersonal schemas, perfectionism, and thought action-fusion in obsessive-compulsive disorder Objective: Cognitive vulnerability factors are central in the etiology of obsessive-compulsive disorder. Nosological classifications among symptom clusters have been developed to enable the understanding of possible mechanisms underlying obsessive compulsive symptoms. Previous researchers have emphasized that perfectionist attitudes and thought action-fusion link to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that TAF is comprised of two assumptions; distress occurs due to the belief a thought will subsequently transpire, and compulsive behaviours are implemented in an attempt to neutralise the outcome (Meyer & Brown, 2012). There is extensive research on the construct of TAF and it has subsequently become one of the most popular and widely accepted cognitive constructs of OCD (Aydin et al, 2012;O'Leary, Rucklidge, & Blampied, 2009).…”
Section: Thought -Action Fusionmentioning
confidence: 99%
“…It has been suggested that TAF is comprised of two assumptions; distress occurs due to the belief a thought will subsequently transpire, and compulsive behaviours are implemented in an attempt to neutralise the outcome (Meyer & Brown, 2012). There is extensive research on the construct of TAF and it has subsequently become one of the most popular and widely accepted cognitive constructs of OCD (Aydin et al, 2012;O'Leary, Rucklidge, & Blampied, 2009).…”
Section: Thought -Action Fusionmentioning
confidence: 99%